The Effect of Financial Performance as Moderating on Good Corporate Governance, Media Exposure and Disclosure of Sustainability Reports - Afridayani, Afridayani; Holiawati, Holiawati; Ruhiyat, Endang (EAJ (Economic and Accounting Journal), 2023)
This study aims to determine the Influence of Good Corporate Governance and media Exposure on the Disclosure of Sustainability Reports with Financial Performance as a Moderating Variable. This type of research is quantitative research with research data in the form of annual reports and sustainability reports of 50 companies on the Indonesia Stock Exchange in 2019 - 2021, which are downloaded via the official website of the Indonesia Stock Exchange and the websites of companies that are used as research samples. The result shows that Good Corporate Governance does not affect the disclosure of sustainability reports. Media exposure influences the disclosure of sustainability reports. Financial Performance, without effect, moderates the relationship between good corporate governance and sustainability report disclosure. The finding also reveals that Financial Performance was without effect moderate on the relationship between Good Corporate Governance variables and Sustainability Report disclosure. The novelty in this study is to add financial Performance as moderating concerning good corporate governance on disclosure of sustainability reporting and concerning media exposure on disclosure of sustainability reporting.